Ab initio Morse/long-range potential energy functions plus spectroscopic and thermophysical properties of heteronuclear diatomic complexes of xenon with the rare gases. (July 2022) - Liu, Jia; Zhai, Yu; Li, Hui; McCourt, Frederick R.W.
Highlights: High-fidelity ( d d < 1.51 ) Morse/long-range potential energy functions for the Xe-He, Xe-Ne, and Xe-Ar dimers are developed using only 13 parameters, which are determined by state-of-the-art ab initio PECs. Ro-vibrational energy levels and absorption spectra are computed and achieve good agreement with existing experimental values. The second virial coefficient and transport properties of dilute gases are computed from purely theoretical work and obtain accurate values which are in good agreement with the experimental data. Abstract: New interatomic potential energy curves of xenon-helium (Xe-He), xenon-neon (Xe-Ne), and xenon-argon (Xe-Ar) atom pairs are developed by state-of-the-art ab initio calculations. Coupled cluster theory with single, double, and perturbative triple excitations [CCSD(T)] is used to calculate the majority of the interaction between atoms, on (multiple) augmented correlation-consistent basis sets for valence orbitals, extrapolated to the complete basis set (CBS) limit. Contributions from inner nuclear electronic correlation, relativistic effects, and higher-order excitations beyond CCSD(T) are also considered as corrections. For each system, an analytical Morse/long-range (MLR) potential functions, is fitted to 32 ab initio data using only 13 parameters: the poorest-quality fit yielded a dimensionless-root-mean-square-deviation ( d d ¯ ) of only 1.51. The ro-vibrational energy levels and wave functions, resonance states, effective radial potential energy curves, absorption spectra and thermophysical properties have also been computed.